Big Pig on a dig - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (Tulsa, Okla. : EDC Pub., 1999)
Big Pig makes a surprising discovery in his quest to dig for gold.
"Simple phonics reader"--Cover.
Lift the flap pages.
1.0.
1.0
K-3
Keywords: Toy and movable books -- Specimens; Buried treasure -- Fiction; Pigs -- Fiction; Toy and movable books; Buried treasure -- Fiction; Pigs -- Fiction; Toy and movable books